2015
DOI: 10.3390/w7105566
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Performance of In-Stream Restoration Projects Using Radio Frequency Identification (RFID) Transponders

Abstract: Abstract:Instream channel restoration is a common practice in river engineering that presents a challenge for research. One research gap is the development of monitoring techniques that allow for testable predictions of sediment transport and supply. Here we use Radio Frequency Identification (RFID) transponders to compare the short-term (1-year) sediment transport response to flood events in a restored and a control reach. The field site is Wilket Creek, an enlarged creek in a fully urbanized catchment withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 75 publications
(105 reference statements)
1
23
0
Order By: Relevance
“…Restoration efforts, once both the flow and channel are changed, will require an integrated approach. For instance, there may be opportunities to accompany catchment‐scale flow mitigation works with promotion of self‐regeneration of stream morphology including sediment seeding and the stream self‐organizing sediments (MacVicar, Chapuis, Buckrell, & Roy, ; Wilcock, ) to minimize erosion and mobility. In other cases, direct intervention to modify the channel morphology may need to accompany the flow mitigation effort.…”
Section: Discussionmentioning
confidence: 99%
“…Restoration efforts, once both the flow and channel are changed, will require an integrated approach. For instance, there may be opportunities to accompany catchment‐scale flow mitigation works with promotion of self‐regeneration of stream morphology including sediment seeding and the stream self‐organizing sediments (MacVicar, Chapuis, Buckrell, & Roy, ; Wilcock, ) to minimize erosion and mobility. In other cases, direct intervention to modify the channel morphology may need to accompany the flow mitigation effort.…”
Section: Discussionmentioning
confidence: 99%
“…Categorical mapping of sediment storage areas (gravel bars, age of riparian vegetation) based on how often sediment has moved can also be used to estimate areas of channel and floodplain sediment storage (Madej, ; Pess et al, ). PIT tags (radio frequency identification [RFID] transponders) can also be used to examine sediment transport (MacVicar, Chapuis, Buckrell, & Roy, ). Many of these approaches are only feasible for very intensive monitoring of one or a few floodplain restoration projects.…”
Section: Review Of Methods For Monitoring Floodplain Restorationmentioning
confidence: 99%
“…Questions about the costs of ongoing maintenance and the possibility of ameliorating the ecosystem services of urban creeks and rivers led to a city-wide hydrologic and geomorphic study in the 1990s (D'andrea et al, 2004). A study of the impact of this approach on sediment dynamics showed it successfully reduced the frequency of transport decreased for gravel and cobble sized material (MacVicar et al, 2015) though the long-term implications remain uncertain. Several floods in the 2000s caused widespread erosion of natural and previously stabilized bed and banks (Figure 2), which led to the creation of a stabilization plan to control erosion and minimize the risk to infrastructure in the watershed (Parish Geomorphic, 2011).…”
Section: Site Descriptionmentioning
confidence: 99%
“…A significant portion of the lower reach (~1 km or 50%) has now been rebuilt following a constructed riffle-pool approach. A study of the impact of this approach on sediment dynamics showed it successfully reduced the frequency of transport decreased for gravel and cobble sized material (MacVicar et al, 2015) though the long-term implications remain uncertain. The question of channel enlargement and an appropriate model for channel evolution in response to urbanization remain of significant interest for guiding future management efforts.…”
Section: Site Descriptionmentioning
confidence: 99%